(untitled) (Comparative & International Education Series, 2021)
The forced modality transition to online learning created panic and concern about the quality of education received by students worldwide. While e-learning and distance learning are not new practices, most faculty did not have the training or resources for the appropriate design of online courses to promote student success. The pandemic pedagogy created by COVID-19 placed students and faculty into an unfamiliar online realm filled with uncertainty, technology failures, and equity issues. This chapter will review the design of authentic online courses amid a pandemic through a brief case study of an institution given three days to transition to online learning and the challenges faced by faculty and limited staff in the Office of the Online Campus. The transition from a lecture-based in-person course to a fully online course with social distancing is challenging, though faculty and students can excel in the course through proper design and pedagogy.